Social comparison effects on students’ cognitive anxiety, self-confidence, and performance in Chinese composition writing - Hong, Jon-Chao; Tai, Kai-Hsin; Hwang, Ming-Yueh; Lin, Chia-Yin (Frontiers in Psychology, 2022)
Social comparison is a mind-altering determinant that affects students’ learning behavior. To understand the effect, three instructional approaches to teaching Chinese writing skills were designed and implemented in this study: (1) The No Comparison Group (NCG): students were asked to complete compositions on their own; (2) The Upward Comparison Group (UCG): superior composition examples were provided and the students were asked to write compositions on the same topics; and (3) The Downward Comparison Group (DCG): inferior examples were provided for students to critique. Taiwanese junior high school ninth graders participated in three groups, and wrote compositions on six themes. The results revealed that the Chinese composition writing skills of the students in the UCG and DCG improved significantly more than those of the students in the NCG. Composition-prompted cognitive anxiety in the DCG declined substantially. The results imply that adopting upward and downward comparisons for students to practice Chinese composition is worth adopting in writing lessons.